PERANCANGAN PROTOTYPE APLIKASI KNOWLEDGE MANAGEMENT UNTUK MENDUKUNG PROSES KNOWLEDGE SHARING PADA PT. PRIMA CIPTA MANDIRI SEJATI - DONI ANDRIANSYAH (Paradigma, 2015)
diversity of knowledge that can be used as a valuable asset to the company. With so many events that have been conducted, it should be able to carry out PCM event better than the previous event. However, the lack of documentation of knowledge of the results of the implementation of the event resulted in the same error in the implementation of the next event. This is because there is no proper management of knowledge that has been owned by the company that it can not be used as a reference study for the implementation of the next event. The purpose of this study is to provide a means of documentation and implementation of event knowledge storage well that employees and companies that can be easily accessed and distributed to all employees. This type of research is descriptive. Data was collected through surveys, interviews, and documentation. System design method used is the 10-Step of KM Road Map. The results of this study is a prototype application knowledge management system (KMS) in which there are features that are needed in the process of knowledge sharing in PCM.